RANCANG BANGUN PEMECAH KULIT PADI DENGAN PENGATURAN KECEPATAN MOTOR DENGAN METODE FUZZY - Tandra, Stefanus Ardyanto; Harianto, Harianto; Susanto, Pauladie (Journal of Control and Network Systems, 2015)
Currently many farmers who use bran-breaking machine on the market, but there is a disadvantage that efiensi usage. In this study bran crusher motor to drive breaker controlled amount of paddy rice that gets broken skin. For his future is expected this study can be used to help farmers in order to regulate fuel efficiency. The purpose of the design and manufacture of these devices is How to improve engine performance broke the skin becomes automatic. How to make a fuzzy system to control the speed of the motor. How to create a user interface that is easy to use by the user. After further investigation the author uses the methods used in this problem is the fuzzy method, because it is flexible in the sense that the method is able to adapt to the changes that are influenced by the environment. Fuzzy method is divided into three methods: mamdani, Sugeno, and sukamoto. In this case I use the Sugeno method for research. There are several processes through which to control the motor speed breaker bran. The process is fuzzyfikasi, ruleset, and defuzzyfication. Through the process is expected to be the motor rotates in accordance with the amount of rice in the bin. The result of the process is a fuzzy PWM value (Pulse Width Modulation), and will be displayed on the LCD. From this study, the motor moves faster when rice is very much in the bin, the more slowly when the rice in the bin on the wane. And will stop when there are no rice in the bin.